APLIKASI ARSITEKTUR HEALING ENVIRONMENT PADA RANCANGAN PUSAT REHABILITASI SOSIAL TERPADU PROVINSI GORONTALO - Paca, Nurhadiningsi; Pratiwi, Niniek; Saman, Satar (Universitas Negeri Gorontalo, 2024)
Pancasila and the 1945 Constitution of the Republic of Indonesia mandate that the state has the responsibility to protect the entire Indonesian nation and promote public welfare in the framework of realizing social justice for all Indonesian people. Integrated Social Rehabilitation Center as a place for rehabilitation or recovery and development to enable a person, namely PPKS, to carry out his social functions normally. The design of the Integrated Social Rehabilitation Center in Gorontalo Province was due to the unavailability of Integrated Social Rehabilitation Center facilities in Gorontalo, both as part of the service and as an institution. Based on the results of a field survey, Gorontalo Province does not yet have a Social Rehabilitation Institution, this has become the government's impetus to plan the development of a Social Rehabilitation Institution with a centralized concept in 2025. The building design method is based on all relevant data. This data is obtained from various literature, journals, books according to the design object problems. After collecting the next data in the analysis stage, namely using descriptive analysis methods. Data covering everything related to the Integrated Social Rehabilitation Center and the Healing Environment architecture were obtained, then elaborated and analyzed, the analysis was used as reference material for planning concepts. The design of the building maximizes aspects, namely lighting, especially natural lighting, indoor ventilation, the use of parks and outdoor spaces and an organized spatial arrangement with attention to user comfort. This building carries the theme of Environmental Healing Architecture which applies three elements namely nature, senses and psychology based on the function of the Social Rehabilitation Center. Pancasila dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 mengamanatkan negara mempunyai tanggung jawab untuk melindungi segenap bangsa Indonesia dan memajukan kesejahteraan umum dalam rangka mewujudkan keadilan sosial bagi seluruh rakyat Indonesia. Pusat Rehabilitasi Sosial Terpadu sebagai wadah rehabilitasi atau pemulihan dan pengembangan untuk memungkinkan seseorang yakni Pemerlu Pelayanan Kesejahteraan Sosial (PPKS) mampu melaksanakan fungsi sosialnya secara wajar. Perancangan Pusat Rehabilitasi Sosial Terpadu di Provinsi Gorontalo ini dikarenakan belum tersedianya fasilitas Pusat Rehabilitasi Sosial Terpadu di Gorontalo, sebagai bagian pelayanan dan panti. Berdasarkan hasil survey lapangan Provinsi Gorontalo belum mempunyai Panti Rehabilitasi Sosial, dengan ini menjadi dorongan pemerintah untuk merencanakan pembangunan Panti Rehabilitasi Sosial dengan konsep tepusat pada tahun 2025. Adapun metode perancangan desain bangunan berdasar dari data-data keseluruhan yang terkait. Data ini diperoleh dari berbagai literatur, jurnal, buku-buku sesuai dengan permasalahan objek perancangan. Setelah melakukan pengumpulan data selanjutnya pada tahapan analisis yakni menggunakan metode analisis deskriptif. Data yang mencakup keseluruhan terkait Pusat Rehabilitasi Sosial Terpadu dan arsitektur Healing Environment yang diperoleh, kemudian dijabarkan dan di analisis, Analisis–analisis ini sebagai bahan acuan konsep perencanaan. Desain bangunan memaksimalkan aspek-aspek yakni pencahayaan terutama pada pencahayaan alami, penghawaan pada ruangan, penerapan taman dan ruang luar serta pengorganisasian ruang yang tertata dengan mempertimbangkan kenyamanan pengguna. Bangunan ini mengusung tema Arsitektur Healing Environment yang mengaplikasikan tiga unsur yakni alam, indra dan psikologis berdasarkan fungsi dari Pusat Rehabilitasi Sosial.